2021
DOI: 10.1111/1365-2656.13507
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of radiation exposure on the bacterial and fungal microbiome of small mammals in the Chernobyl Exclusion Zone

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(66 citation statements)
references
References 87 publications
1
63
2
Order By: Relevance
“…We have estimated total absorbed dose rates for relevant organism types rather than simply using ambient dose rate as a marker of comparative radiation levels across our study sites. In agreement with previous observations [ 44 , 75 , 76 ] we demonstrated that ambient dose rate underestimated total absorbed dose rates to organisms. We recommend that, when relating observations to radiation exposure, total absorbed dose rates are used.…”
Section: Discussionsupporting
confidence: 93%
“…We have estimated total absorbed dose rates for relevant organism types rather than simply using ambient dose rate as a marker of comparative radiation levels across our study sites. In agreement with previous observations [ 44 , 75 , 76 ] we demonstrated that ambient dose rate underestimated total absorbed dose rates to organisms. We recommend that, when relating observations to radiation exposure, total absorbed dose rates are used.…”
Section: Discussionsupporting
confidence: 93%
“…In Antwis et al (2021), we make a comment that 'any study that uses the Red Forest as a location for radiation effect studies on wildlife needs to consider the historical impacts of radiation and other stressors (e.g. wildfires) on this area'.…”
Section: Con S Ider Ati On S On S Tud Ie S In R Adiolog Ic Ally Conta...mentioning
confidence: 99%
“…Similarly, gut mycobiota in two species of wild mice were dominated by yeasts assigned to the genus Kazachstania , but contained SV groups assigned to a polypore, Trametes versicolor [ 33 ]. Further, SV groups assigned to macrofungi ( Steccherinaceae and Strophariaceae , which include polyporoid and mushroom-forming species, respectively) form an abundant component of the apparent gut mycobiota of small rodents [ 34 ]. Indeed, SV groups assigned to macrofungi and plant pathogens or endophytes occur in analyses of gut mycobiota of diverse wild animal taxa, including macaques [ 35 ], bats [ 18 ], zebrafish [ 36 ], and birds [ 33 , 37 ].…”
Section: Separating the Wheat From The Chaff: Non-resident Fungi Are Present In Analyses Of Wild Animal ‘Gut Mycobiota’mentioning
confidence: 99%
“…For example, one response of the fungal community in fecal samples from yellow-necked mice inhabiting ecosystems that had experienced different levels of burning was a change in abundance of Gelatoporia sp. [ 34 ]. Since Gelatoporia is a genus of poroid crust fungi producing white rot that inhabits dead wood [ 38 ], these data may reflect the condition of the host’s environment and diet rather than an effect of environment on the resident gut mycobiota per se.…”
Section: Separating the Wheat From The Chaff: Non-resident Fungi Are Present In Analyses Of Wild Animal ‘Gut Mycobiota’mentioning
confidence: 99%
See 1 more Smart Citation